2020
DOI: 10.3389/fimmu.2020.567391
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Mesenchymal Stem Cells in Oral Mucosal Bacterial Immunotherapy

Abstract: Recent clinical observations indicate that bacterial vaccines induce cross-protection against infections produced by different microorganisms. MV130, a polyvalent bacterial sublingual preparation designed to prevent recurrent respiratory infectious diseases, reduces the infection rate in patients with recurrent respiratory tract infections. On the other hand, mesenchymal stem cells (MSCs) are key cell components that contribute to the maintenance of tissue homeostasis and exert both immunostimulatory and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Oral MSCs are adult stromal cells, which are distinguished by their ability to self-renew and to give rise to different cell lines (bone, fat, chondrocytes, muscles, neurons, islet cells, liver cells) [ 9 ]. In the body, adult stem cells are responsible for regular tissue maintenance as well as regenerating new tissue parts in response to injury or disease and their business can be affected in many different ways [ 10 , 11 ]. Oral tissues such as dental pulp and periodontal ligament can be used as alternative sources of MSCs compared to the well-known adult tissues (bone marrow, adipose tissue, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Oral MSCs are adult stromal cells, which are distinguished by their ability to self-renew and to give rise to different cell lines (bone, fat, chondrocytes, muscles, neurons, islet cells, liver cells) [ 9 ]. In the body, adult stem cells are responsible for regular tissue maintenance as well as regenerating new tissue parts in response to injury or disease and their business can be affected in many different ways [ 10 , 11 ]. Oral tissues such as dental pulp and periodontal ligament can be used as alternative sources of MSCs compared to the well-known adult tissues (bone marrow, adipose tissue, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, the polybacterial mucosal vaccine MV130 has been shown to be effective in preventing RTI recurrences in either adults ( Alecsandru et al., 2011 ; García González and Arrutia Díez, 2019 ) or children ( Nieto et al., 2021 ). Although the action of MV130 has been studied in different cell types ( Cirauqui et al., 2018 ; Molero-Abraham et al., 2019 ; Vázquez et al., 2020 ), a clear mechanism of protection is still unidentified. Prevention of RTI recurrences in children points to an antiviral effect, as wheezing attacks in young children are predominantly linked to respiratory virus infections ( Jartti et al., 2019 ; Meissner, 2016 ; Le Souëf, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a phase 3 randomized, double-blind, placebo-controlled trial (NCT01734811), children treated with MV130 showed an important reduction in the incidence and severity of recurrent wheezing ( Nieto et al., 2021 ), a condition associated with viral infections ( Jartti et al., 2019 ; Le Souëf, 2018 ). The immunomodulatory properties of MV130 have been studied on dendritic cells (DCs) ( Cirauqui et al., 2018 ), oral epithelial cells ( Molero-Abraham et al., 2019 ), and mesenchymal stem cells ( Vázquez et al., 2020 ). However, the mechanisms underlying the broad anti-infectious protection provided by MV130 remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have attracted considerable attention in various fields of medicine (45). However, research on the safety and effectiveness of the clinical application of MSCs is still in the early stages and many obstacles remain to be addressed, such as how to optimize the reparative potential of MSCs, how to regulate their abnormal proliferation and tumorigenesis ability, and how to regulate the relationship between MSCs and other immune cells (46)(47)(48). Potter found that MSC and MSC-EVs attenuate lung injury after THS by regulating the GTPase RhoA (49).…”
Section: Discussionmentioning
confidence: 99%